HUMAN RESOURCE CHARACTERISTICS OF THE AGRICULTURAL SECTOR IN NORTH SULAWESI - Putu Purba Padma Pratiwi (Universitas Tadulako, 2020)
The agricultural sector in North Sulawesi is ranked first in its role in providing added value to the GRDP and labor. However, the rate of growth of production and labor productivity is relatively low and decreases over time. Building the agricultural sector is limited to the development of subsistence farming and increases human resources or competence in the farming business. This study aimed to identify the characteristics of farmers in North Sulawesi. The results of the descriptive statistical analysis using demographic, socioeconomic, and socio-cultural variables of farmers indicate that the quality of human resources in the agricultural sector in North Sulawesi is relatively low. Thus, government policies to improve the quality of the agricultural sector's human resources is urgently needed.